The Pandora"s box of frailty assessments, which is the best for clinical purpose? A critical review. (11th May 2021) - Baritello, O; Salzwedel, A; Suendermann, S; Niebauer, J; Voeller, H
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Assessment of frailty is recommended for patients undergoing elective transcatheter aortic valve implantation (TAVI) to appreciate post-interventional prognosis. Several studies investigated frailty in this population using single markers (e.g. gait speed), clinical judgment scales (e.g. Rockwood) or composite indexes (e.g. Fried). However, there is a lack of consensus on the most appropriate tool for assessment of frailty in clinical practice. Purpose: To evaluate which frailty assessment is the most used and meaningful for post-interventional prognosis in older TAVI patients. Methods: A systematic search was performed in PubMed (May 2020). We included randomized controlled trials or observational studies (prospective or retrospective) without time restrictions investigating the association of frailty and 1-year all-cause mortality in older (≥70 years) TAVI-patients. Results: 60 studies (151, 723 patients) were included. Studies heterogeneity (methods) was considerable. 40 different frailty assessments were identified. The most used single marker (Table) was gait speed (5-meter walk test), investigated in 16 observational studies (8/8 prospective/retrospective with 5, 747/40, 535 patients). 11 studies found mortality prediction by reduced gait speed, with hazard ratios (HR) between 1.36 (95% confidence interval (CI) 1.23-1.50) and 14.71 (95%CI 6.50-33.30) as well as an Odds Ratio (OR) of 2.34 (95%CI 1.03-5.32). Frailty in composite indexes (Table) predicted mortality in 10 of 11 observational studies 4-items index: HR 1.84 (95%CI 1.23-2.69) to 3.05 (95%CI 1.24-7.46), 5-items index: OR 1.63 (95 CI 1.12-2.37) to 2.75 (95%CI 1.55-4.87). Conclusion: Predominantly, single markers, especially gait speed, are used to assess frailty in TAVI-patients. Composite indexes seem to be relieble as well and should be considered for prediction of 1-year mortality.